BIM's Contribution as A Sustainable Construction Accelerator - Nindyo Cahyo Kresnanto; Raihan Iqbal Ramadhan; Muhamad Willdan; Panca Buana Pamungkas Putra (POLITEKNIK NEGERI JAKARTA, 2023)
Building Information Modeling (BIM) is a technological tool used in the sustainable construction process, beginning with the planning phase and continuing through the construction and post-construction phases. BIM has excellent capabilities and is being adopted by construction service providers in the process of implementing sustainable construction. However, many barriers remain in the adoption process, particularly with regard to the intention to use it. The purpose of this study was to determine the intention to implement BIM based on the variables of benefits and barriers. In order to parse the phenomena that occur in research, this study employed a quantitative method. Survey data in the form of a questionnaire were collected from the Special Region of Yogyakarta using a purposive sampling method for this study. Questionnaires were distributed via Google Form to respondents from the construction sector (Civil & Architectural Engineering) and BIM application users (students, workers). The findings of this study have provided an overview of the challenges and benefits of implementing BIM in sustainable construction. The barriers presented are financial, technological, and policy barriers, depending on the company's classification, while the benefits presented are environmental benefits and innovation.